Impact of carpal tunnel surgery according to pre-operative abnormality of sensory conduction in median nerve: a longitudinal study. - Coggon, D; Ntani, G; Harris, E; Linaker, C; Van der Star, R; Cooper, C; Palmer, K (BioMed Central, 2013)
BACKGROUND: We have previously proposed that sensory nerve conduction (SNC) in the median nerve should be classed as abnormal when the difference between conduction velocities in the little and index fingers is > 8 m/s. In a prospective longitudinal study, we investigated whether this case definition distinguished patients who were more likely to benefit from surgical treatment. METHODS: We followed up 394 patients (response rate 56%), who were investigated by a neurophysiology service for suspected carpal tunnel syndrome. Information about symptoms, treatment and other possible determinants of outcome was obtained through questionnaires at baseline and after follow-up for a mean of 19.2 months. Analysis focused on 656 hands with numbness, tingling or pain at baseline. Associations of surgical treatment with resolution of symptoms were assessed by Poisson regression, and summarised by prevalence rate ratios (PRRs) and associated 95% confidence intervals (95% CIs). RESULTS: During follow-up, 154 hands (23%) were treated surgically, and sensory symptoms resolved in 241 hands (37%). In hands with abnormal median SNC, surgery was associated with resolution of numbness, tingling and pain (PRR 1.5, 95% CI 1.0-2.2), and of numbness and tingling specifically (PRR 1.8, 95% CI 1.3-2.6). In contrast, no association was apparent for either outcome when median SNC was classed as normal. CONCLUSIONS: Our definition of abnormal median SNC distinguished a subset of patients who appeared to benefit from surgical treatment. This predictive capacity gives further support to its validity as a diagnostic criterion in epidemiological research.